OBO-Fused Benzo[fg]tetracene as Acceptor With Potential for Thermally Activated Delayed Fluorescence Emitters - Zhang, Zhen; Kumar, Shiv; Bagnich, Sergey; Spuling, Eduard; Hundemer, Fabian; Nieger, Martin; Hassan, Zahid; Köhler, Anna; Zysman-Colman, Eli; Bräse, Stefan (Frontiers in Chemistry, 2020)
Six luminophores bearing an OBO-fused benzo[fg]tetracene core as an electron-acceptor were designed and synthesized. The molecular structures of three molecules (PXZ-OBO, 5PXZ-OBO, 5DMAC-OBO) were determined by single crystal X-ray diffraction studies and revealed significant torsion between the donor moieties and the OBO acceptor with dihedral angles between 75.5° and 86.2°. Photophysical studies demonstrate that blue and deep blue emission can be realized with photoluminescence maxima (λPL) ranging from 415 nm to 480 nm in mCP films. The emission energy is modulated by simply varying the strength of the donor heterocycle, the number of donors and their position relative to the acceptor. Although the DMAC-derivatives show negligible delayed emission due to their large singlet-triplet excited state energy difference, ΔEST, PXZ-based molecules, especially PXZ-OBO with an experimental ΔEST of 0.25 eV, demonstrate delayed emission in blend mCP films at room temperature, which suggests triplet exciton harvesting occurs in these samples, potentially by thermally activated delayed fluorescence (TADF).